Weight cutting in female UFC fighters - Cassandra Evans; Charles Stull; Gabriel Sanders; Anthony Ricci; Duncan French; Jose Antonio; Corey A. Peacock (Taylor & Francis Group, 2023)
Background It is common practice for fight sport athletes to use a variety of weight manipulation strategies to compete in desired weight classes. Although numerous studies have highlighted rapid weight loss (RWL) strategies and the magnitude of weight loss, few have focused specifically on weight loss in female fighters. The purpose of this study was to provide descriptive information on professional UFC female fighters engaging in RWL in all women's UFC weight divisions: strawweight (52.2 kg): flyweight (56.7 kg); bantamweight (61.2 kg); featherweight (65.8 kg). Methods All fighter's weights were obtained at five separate time points: 72 hrs. pre-weigh-in, 48 hrs. pre-weigh-in, 24hrs. pre-weigh-in, official weigh-in, and 24 hrs. post-weigh-in (competition weight). Mixed effects models and random effects analysis were used to assess changes in weight and differences between weight divisions. All statistics were analyzed, and significance was set at p ≤0.05. Significant changes in weight between all time points were reported. Results No statistical differences between weight divisions were observed. Female fighters lost 4.5-6.6% of their weight prior to the official weigh-in. Conclusion Females engaged in RWL practices lose weight in a similar fashion irrespective of weight class.